Fusogenic Liposomes Increase the Antimicrobial Activity of Vancomycin Against Staphylococcus aureus Biofilm - Scriboni, Andreia Borges; Couto, Verônica Muniz; Ribeiro, Lígia Nunes de Morais; Freires, Irlan Almeida; Groppo, Francisco Carlos; de Paula, Eneida; Franz-Montan, Michelle; Cogo-Müller, Karina (Frontiers in Pharmacology, 2019)
The aim of the present study was to encapsulate vancomycin in different liposomal formulations and compare the in vitro antimicrobial activity against S. aureus biofilms. Large unilamellar vesicles of conventional (LUV VAN), fusogenic (LUVfuso VAN), and cationic (LUVcat VAN) liposomes encapsulating VAN were characterized in terms of size, polydispersity index, zeta potential, morphology, encapsulation efficiency (%EE) and in vitro release kinetics. The formulations were tested for their Minimum Inhibitory Concentration (MIC) and inhibitory activity on biofilm formation and viability, using methicillin-susceptible S. aureus ATCC 29213 and methicillin-resistant S. aureus ATCC 43300 strains. LUV VAN showed better %EE (32.5%) and sustained release than LUVfuso VAN, LUVcat VAN, and free VAN. The formulations were stable over 180 days at 4 °C, except for LUV VAN, which was stable up to 120 days. The MIC values for liposomal formulations and free VAN ranged from 0.78 to 1.56 µg/mL against both tested strains, with no difference in the inhibition of biofilm formation as compared to free VAN. However, when treating mature biofilm, encapsulated LUVfuso VAN increased the antimicrobial efficacy as compared to the other liposomal formulations and to free VAN, demonstrating a better ability to penetrate the biofilm. Vancomycin encapsulated in fusogenic liposomes demonstrated enhanced antimicrobial activity against mature S. aureus biofilms.